Asian Yearbook of International Law, Volume 7 (1997) - Swan, Sik Ko; Pinto, M. C. W.; Subedi, Surya (Asian Yearbook of International Law ;, 2001)
The Asian Yearbook of International Law is the first publication dedicated primarily to international law as seen from an Asian perspective. It provides international law articles written by experts from the region and other articles relating to Asian topics. The editorial board, national correspondents, advisory council, and governing board comprise a diverse group of academics and government officials from a wide range of countries and positions. The Asian Yearbook of International Law offers a number of useful features: - articles;- notes; - legal materials (such as the state practice in a number of Asian countries and participation in multilateral treaties); - Asia and international organizations; - chronicle of events for the covered year; - literature (including book reviews and a bibliography); - selected documents (treaties, agreements, and other relevant primary documents); and - an index. Its range of features assures that the Yearbook comprehensively covers the critical events, legislation, and issues of the past year and that users can easily access all of this information. Academics and practitioners who deal with international public law in Asia will appreciate this unique, complete resource. The Asian Yearbook of International Law provides insight into Asian views and practices, especially for non-Asian readers, and also promotes the dissemination of knowledge of international law in Asia. Some of the topics covered in this volume: the secession of Bangladesh in international law; the Asian Development Bank Administrative Tribunal; port state control: a comment on the Tokyo MOU; maritime jurisdiction over vessel-source pollution in the EEZ: the Chinese experience.